PENGGUNAAN RANTAI SEBAGAI ALAT BANTU MENGURANGI SELIP DALAM PENGANGKUTAN KAYU - Yuniawati; Dulsalam; Sukadaryati (BRIN Publishing, 2013)
The use of trucks in log hauling has many advantages, however tire slip can pose serious problem. Tire slip is not onlyloss in term of log production efficiency, but also damaging the soil road surfaces. Tire chain is one of alternative method toavoid tire slip. This paper studies to find out the slip and the effect of the use of tire chain into the soil damage. The resultsshowed that the use of tire chain was able to reduce the average of tire slip by 95.98%. The average tire slip in normal tirewas 24.85% in the 82.82% moisture content, while the slip in chain added tire was 12.68% in the 84.63% moisturecontent. The use of tire chain can reduce slip and the depth of tire tracks significantly